1991
DOI: 10.1093/carcin/12.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of GST-P positive liver cell foci development by combined treatment of rats with five heterocyclic amines at low doses

Abstract: Potential synergism between five heterocyclic amines at low doses was evaluated in a medium-term liver bioassay system for carcinogens. F344 male rats were given a single i.p. injection of diethylnitrosamine (DEN, 200 mg/kg) and then received test compound(s) in their diet for 6 weeks beginning 2 weeks later. Control groups received DEN or test compound(s) alone. All rats were subjected to two-thirds partial hepatectomy at week 3 and killed at week 8. Compounds tested and reported positive were 3-amino-1,4-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…As well demonstrated by researchers in Ito's group 20,21,[23][24][25][26] , the medium-term liver bioassay and the medium-term multiorgan model are plausible alternatives to long-term studies. Particularly, in the medium-term liver bioassay, the endpoints, the numbers and areas of GST-P positive liver foci, allow very sensitive evaluation of the tumorigenicity of test compounds in the liver, and this model is particularly appropriate for investigating summation, synergism, or inhibition of carcinogenic responses with mixtures of multiple chemicals.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As well demonstrated by researchers in Ito's group 20,21,[23][24][25][26] , the medium-term liver bioassay and the medium-term multiorgan model are plausible alternatives to long-term studies. Particularly, in the medium-term liver bioassay, the endpoints, the numbers and areas of GST-P positive liver foci, allow very sensitive evaluation of the tumorigenicity of test compounds in the liver, and this model is particularly appropriate for investigating summation, synergism, or inhibition of carcinogenic responses with mixtures of multiple chemicals.…”
Section: Discussionmentioning
confidence: 94%
“…Genotoxic carcinogens like nitrosamines and HCAs induce DNA damage through formation of DNA adduct(s) and/or oxygen radical species produced as bi-products and alteration of the genome is thought to be irreversible once it has take place, leading to the assumption that risks may be additive even at low doses. The data demonstrated by Burger 10 and Ito's group [23][24][25] , however, provide evidence that combination treatment with genotoxic carcinogens at low doses does not necessarily entail additive risk for carcinogenicity. This phenomenon could be partly explained by detoxification of carcinogens administered and/or successful repair of DNA damage caused by low doses of carcinogens.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, concurrent treatment with low doses of 3 N -nitroso compounds (genotoxic carcinogens) did not show additive effects on liver tumor development; only treatment with high doses exerted an additive effect 8 . Furthermore, concurrent treatment with low doses of 5 or 10 heterocyclic amines did not enhance development of preneoplastic lesions of the liver either additively or synergistically when given at the post-initiation stage in medium-term live bioassays (Ito test) 9 , 10 , 11 . These findings suggested that concurrent treatment with genotoxic carcinogens at low doses did not necessarily entail additive risk for carcinogenicity 7 .…”
Section: Introductionmentioning
confidence: 90%